Compliance with National Speech Therapy Standards: A Comparative Assessment of Two Government Hospitals in Central Java - Gunawan, Gunawan; Sukmakarti, Laksmy Dewi; Nugroho, Setyadi (Interest : Jurnal Ilmu Kesehatan, 2025)
Background: Standardisation of speech therapy services ensures consistent quality and reduces performance gaps between facilities within the Indonesian healthcare system. However, compliance remains inconsistently implemented across government hospitals, creating variations in service quality and patient outcomes. This study aimed to measure the compliance level of speech therapy services in two government hospitals with Minister of Health Regulation No. 81/2014. Methods: Descriptive quantitative study was conducted at two government hospitals in Central Java. Purposive sampling was used to select five speech therapists as informants. Data were collected through structured checklists aligned with 41 parameters from the regulation. Compliance was scored numerically (1-5 per parameter) and converted into percentages. Total scores were categorized into ratings (A=164-205; B=123-163; C=82-122; D=41-81; E=0-40). Results: Hospital A scored 146/205 (71.21%, Rating B), with deficiencies in screening tools (score: 2/5), documentation validation (2/5), and staff development programs (2/5). Hospital B scored 185/205 (90.24%, Rating A), demonstrating full compliance in interdisciplinary collaboration (5/5) and documentation (5/5). Conclusion: Compliance with national standards varies significantly between hospitals. Standardization of resources and staff training is essential to improve service quality.